Sosialisasi Pembelajaran Pencak Silat Pada Anak Sekolah Dasar - Handayani, Heni Yuli; Purwoto, Septyaningrum Putri; Nurul Jahsy, Aisyah Vinka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Pencak silat learning is given from the elementary school level. Pencak silat material in the substance of PJOK makes a real contribution to achieving national education goals. Pencak silat contains learning elements that are very good for the growth and development of children. Besides that, pencak silat is a heritage of the nation's cultural personality that we must preserve. PEMMAS (Community Service) activities are held at SDK Maria Fatima Bangkalan. In PEMMAS activities, it is divided into the implementation preparation stage. The results obtained include preparing for the delivery of material, delivering material, giving examples of basic silat movements, accompanying them in practice, and practicing together the basic movements of pencak silat. The conclusion that was obtained was that the socialization provided made students very enthusiastic about participating in the socialization, and also students with enthusiasm could practice the basic movements of martial arts well.